Entrepreneurial finance: Analyzing the demand for the personal guarantee - Walter W. Brown; Kent T. Saunders (The Journal of Entrepreneurial Finance (JEF), 2020)
This study contributes to the current body of entrepreneurial finance literature by analyzing multiple aspects of personal guarantees. We conducted a survey yielding 1,462 responses from owners or managers of incorporated small businesses geographically dispersed throughout the United States. Of these, 383 C or S corporations had loans in place during 2014. The survey focuses on personal guarantees used on five types of loans: lines of credit, mortgages, equipment loans, vehicle loans, and a loan type referred to as "other loans." We found the variation increase in personal guarantees for equipment loans, vehicle loans, and other types of loans during the 27 years (1987 - 2014) to be significant with a 95% confidence level, with a 5% margin of error. We found an underinvestment problem (Ang, Lin & Tyler, 1995) exists as 12.5% of owners of incorporated small businesses have decided not to undertake a positive net present value project because the lender required a personal guarantee to obtain a loan for the project. We found lenders denied 10.9% of these 383 corporations a loan resulting in credit rationing because of these corporations' inability to meet the lender's personal guarantee requirements. We found more than 15% of the 383 corporation owners refused the lender's requirement to provide a personal guarantee. Almost 42% of the 15% still received a loan from the same lender after refusing to provide a personal guarantee. We found that only 22.2% of female small-incorporated business owners received a loan after refusing to provide a personal guarantee from the same lender. Compared to 51.4% of the male small incorporated business owners still received the loan after refusing to provide a personal guarantee. Overall, we found that only 37% of the 1,462 incorporated small business respondents had a loan in place during 2014 compared to 67% of incorporated businesses documented by the Federal Reserve Board's 1987 National Survey of Small Business Finances.
Keywords: L26; H81; G00; 650; Personal Guarantee; Small Business Loans